CAUSES OF FINANCIAL CRISIS: THE CASE OF LATVIA - Klyvienė, Violeta; Rasmussen, Lars Tranberg (Ekonomika, 2010)
In this paper, we review how Latvia developed during the boom period and discuss the key structural features of the Latvian economy. We show that a combination of monetary and fiscal expansion contributed to a greater vulnerability to external shocks. We also show that the GDP growth was largely driven by capital deepening, while productivity gains played a significantly smaller role. As a result, one of the most important explanations for the exceptionally deep recession in Latvia should be distortions in the non-traded sectors of the economy. Finally, we give a brief analysis on policy measures that have been taken to correct the distortions and possible pros and cons of an external devaluation.